UJI PERBEDAAN SALINITAS TERHADAP DAYA TETAS TELUR (Hatching Rate) KEPITING BAKAU (Scylla serrata) - Budi Mulyawan; Haryo Triajie; Yudhita Perwitasari (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2010)
Mud crabs (Scylla sp.) is one of marine commodities that is proﬁtable. Mangrove crabs are able to hatch and breed within large variety of salinity. One of the main factors affecting hatching rate and also breeding is salinity. This research is aimed to know the effect of salinity to hatching rate of mud crabs. The design used was complete random sampling through three treatments: those are 15%o, 25%o and 30%o with 3 repetitions. Result of this research shows that hatching rate of mud crabs is affected by salinity. Treatment B (25 %o ) is signiﬁcantly different with treatment A (15%o) and C (30%o). The most appropriate hatching condition is gained from treatment B with average value 91.8%.Keywords: mud crab, Scylla sp, mangroves